2021
DOI: 10.1016/j.expneurol.2021.113709
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of respiratory, autonomic and cardiovascular responses to intermittent hypoxia in humans

Abstract: This review explores forms of respiratory and autonomic plasticity, and associated outcome measures, that are initiated by exposure to intermittent hypoxia. The review focuses primarily on studies that have been completed in humans and primarily explores the impact of mild intermittent hypoxia on outcome measures. Studies that have explored two forms of respiratory plasticity, progressive augmentation of the hypoxic ventilatory response and long-term facilitation of ventilation and upper airway muscle activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 197 publications
(641 reference statements)
1
21
0
Order By: Relevance
“…Abnormal carotid body function also contributes to hypertension, an important comorbidity of SDB (Paton et al, 2013;Del Rio et al, 2016;Narkiewicz et al, 2016;Iturriaga et al, 2021). Animal models of SDB reproducing the recurrent drops in arterial O 2 show that chronic intermittent hypoxia augments the CB's chemosensitivity and reproduce key cardiorespiratory comorbidities observed in SDB patients (Dempsey et al, 2010;Puri et al, 2021). However, chronic intermittent hypoxia is a consequence of SDB and the periodic total or partial obstruction of the upper airway is not reached in this model.…”
Section: Introductionmentioning
confidence: 85%
“…Abnormal carotid body function also contributes to hypertension, an important comorbidity of SDB (Paton et al, 2013;Del Rio et al, 2016;Narkiewicz et al, 2016;Iturriaga et al, 2021). Animal models of SDB reproducing the recurrent drops in arterial O 2 show that chronic intermittent hypoxia augments the CB's chemosensitivity and reproduce key cardiorespiratory comorbidities observed in SDB patients (Dempsey et al, 2010;Puri et al, 2021). However, chronic intermittent hypoxia is a consequence of SDB and the periodic total or partial obstruction of the upper airway is not reached in this model.…”
Section: Introductionmentioning
confidence: 85%
“…Uncoupling of muscle sympathetic nervous system activity and blood pressure following exposure to hypoxia has been reported previously (Cutler et al, 2004a;Cutler et al, 2004b;Lusina et al, 2006;Querido et al, 2010). Local vasodilatory effects of systemic hypoxia could override vasoconstrictor influences from the increased sympathetic outflow resulting in changes in vascular resistance that are unexpected based on sympathetic nervous system activity (Puri et al, 2021). Indeed, Xie et al (2001) reported sustained increases in muscle sympathetic nerve activity following hypoxia without significant modifications in blood pressure or leg blood flow, suggesting that the amount of sympathetic activation was insufficient to raise total peripheral resistance or that the short exposures to hypoxia may not elicit pro-hypertensive mechanisms.…”
Section: Sustained Increases In Minute Ventilation and Systolic Blood...mentioning
confidence: 71%
“…Mild intermittent hypoxia (MIH) is defined by exposure to a few episodes of hypoxia (i.e., no greater than 15 episodes) that are short (i.e., no greater than 4 min) and accompanied by a decrease in oxygen saturation of no less than 85% (Puri et al, 2021). Acute exposure to MIH may result in the initiation of two forms of respiratory plasticity in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a published companion article, we reported that intermittent exposure to concurrent hypoxia and hypercapnia (AIHH: acute intermittent hypercapnic-hypoxia; ~9.5% inspired O 2 ; ~4.5% inspired CO 2 ) elicited robust facilitation of diaphragm motor-evoked potential, MEP, reflection volitional pathways to phrenic motor neurons, and mouth occlusion pressure in 100 msec (P 0.1 ), reflecting automatic ventilatory control, in healthy adults [3]. Combined hypoxia and hypercapnia are more effective at triggering respiratory motor plasticity in humans [4, 5], possibly because greater carotid chemoreceptor activation augments serotonergic raphe neuron activity more than hypoxia alone [6, 7], and/or direct activation of raphe neurons by hypercapnia [8], thereby enhancing cell signaling cascades that strengthen synapses onto phrenic motor neurons. Consistent with published human AIH trials [2], ~40% of participants respond minimally to AIHH (defined as <25% increase in diaphragm MEP amplitudes).…”
Section: Introductionmentioning
confidence: 99%